A Quantitative Model‐Based Assessment of Stony Desert Landscape Evolution in the Hami Basin, China: Implications for Plio‐Pleistocene Dust Production in Eastern Asia. Issue 20 (23rd October 2020) - Abell, Jordan T.; Rahimi, Stefan R.; Pullen, Alex; Lebo, Zachary J.; Zhang, Dehai; Kapp, Paul; Gloege, Lucas; Ridge, Sean; Nie, Junsheng; Winckler, Gisela
Abstract: Dust plays an important role in climate, and while our current representation of dust production includes shifts in vegetation, soil moisture, and ice cover, it does not account for the role of landscape evolution. Here, we use the Weather Research and Forecasting model coupled to an aerosol chemistry model to quantify the effects of arid landscape evolution on boundary layer conditions, dust production, and radiative properties in the Hami Basin, China, a dynamic stony desert in eastern Asia. Relative to today, altered surface roughness, sediment erodibility, and albedo combine to produce up to a 44% increase in wind speeds (mean ≈ 15%), up to a 59% increase in dust loading (mean ≈ 30%), and up to a 4.4 W m −2 increase in downwelling radiation (mean ≈ 2.4 W m −2 ) over the Hami Basin. Our modeling results, along with geomorphological data for the western Gobi Desert, provide evidence that stony deserts acted as important Plio‐Pleistocene dust sources. Plain Language Summary: Dust from the breakdown of rocks and minerals plays an important role in Earth's atmosphere by absorbing or scattering incoming solar radiation, and by seeding clouds. Once deposited, iron‐rich dust can fertilize surface ocean waters and terrestrial soils for the growth of organisms, making dust important in the global carbon cycle. Because of its role in modifying Earth's climate, we must accurately understand ancient dust production. To test the hypothesis that past changes in dust production impacted climate, we altered the surface properties of the western Gobi Desert, a location that had a very different landscape thousands to millions of years ago, and simulated changes in wind and dust using a regional climate model. We found that this area would have experienced increased wind speeds by up to 40%, increased dust loading by up to 60%, and substantially altered incoming solar radiation in response to land surface evolution. Key Points: In arid regions, consideration of landscape evolution is necessary to accurately reconstruct dust production and regional climate We use a regional climate model to quantify the effect of arid landscape evolution on dust production in the Hami Basin, China Representative Plio‐Pleistocene surface conditions lead to enhanced winds and dust production in the Hami Basin relative to today